Les Comédies du Statu Quo - Part II and The Fourth Comédie du Statu Quo 1834 - Doucette, L. E. (Theatre Research in Canada / Recherches théâtrales au Canada, 1982)
An analysis of the composition and historical setting of a series of five short satirical plays published in Québec in the spring of 1834, portraying the protagonists on both sides of the debate concerning the 92 Resolutions. Two of these plays have been ignored until now. There follows the complete text of one of these Comédies du statu quo, virtually unknown and reproduced here for the first time since 1834, with a brief introduction and biographical notes on persons alluded to. Analyse et historique d’une série de cinq courtes pièces satiriques parues à Québec au printemps 1834, deux d’entr’elles inconnues jusqu’ici, et qui mettent en scène les protagonistes de chaque côté du débat sur les 92 Résolutions. Suit une reproduction intégrale de l’une des Comédies du statu quo, restée inédite et pratiquement inconnue depuis 1834, accompagnée d’une courte introduction et de notices biographiques sur les personnages visés.